Salivary gland ultrasound is linked to the autoimmunity profile in patients with primary Sjögren's syndrome. Issue 1 (January 2020) - Nieto-González, Juan Carlos; Ovalles-Bonilla, Juan G.; Estrada, Eduardo; Serrano-Benavente, Belén; Martínez-Barrio, Julia; González-Fernández, Carlos M.; González-Benítez, Roberto; Vergara Dangond, Cristina; Monteagudo, Indalecio; Collado Yurrita, Luis; Naredo, Esperanza; López-Longo, Francisco Javier
Objective: Salivary gland ultrasound (SGU) is a reliable technique for assessing the salivary glands in patients with primary Sjögren's syndrome (pSS). The aim of this study was to elucidate the relationship between SGU findings and autoimmunity in patients with pSS. Methods: Patients with pSS underwent an SGU assessment. The patients were classified into three groups according to their autoimmunity profile: the complete positive group (positive rheumatoid factor, antinuclear antibodies, and anti-Ro/anti-La antibodies), the partial seropositive group (positivity of at least one autoantibody but not all), and the seronegative group. Results: In total, 93 patients were evaluated. Eighty-six (92.5%) were female, and their median age was 49.5 years. The median disease duration was 12.3 years. Pathological SGU findings were present in 32 (34.4%) patients [25 of 36 (78.1%) in the complete positive group and 7 of 44 (21.9%) in the partial positive group]. Patients with pathological SGU findings had a shorter disease duration and slightly higher European League Against Rheumatism Sjögren's syndrome disease activity index. Conclusions: The autoimmunity profile and pathological SGU findings are strongly associated with each other in patients with pSS. However, the disease duration does not seem to be related to pathological SGU findings.